Should HIV be a notifiable disease? Old questions with some new arguments - Venter, W D F; Black, A; Allais, L; et al (My University, 2014)
HIV notification enters national debate regularly, often introduced by politicians and supported by many individual healthcare workers. We argue that its proponents advance confused or poorly informed rationales for making HIV notifiable. We present reasons why making HIV notifiable would be inappropriate in South Africa, why the public health benefits of a notification programme are not even likely, and why there are risks of public health and human rights harms.
KM
Keywords: HIV; South Africa; Disease notification